Analisa Pengaruh Technology Acceptance Model (TAM) Pada Aplikasi Pendaftaran Penilaian Training Record Book (Smile 05) Studi Pada PUKP 05 Semarang - Arika Palapa; Iksan Saifudin (Sekolah Tinggi Maritim Yogyakarta, 2021)
The specific purpose of this study is to examine the effect of perceived ease of use, perceived usefulness, and Attitude toward using on the Actual usage of participating in the Training Record Book assessment in using a partial online-based registration application. This study used a sample of 100 participating in the Training Record Book assessment, both from the Academy and the Vocational High School level. The sampling technique in this study was nonprobability sampling with a purposive sampling-method. Based on the research results, it can be concluded as follows: (1) Perceived ease of use affects Attitude toward using, that the easier it is to use an application, it changes the user's attitude to be interested using it. (2) Perceived usefulness has a positive and significant effect on Attitude toward using, the more useful an application is in accelerating a work process,it changes the user's attitude to be interested in using it. (3) Perceives ease of use has a positive and significant effect on Actual usage, the easier it is to use an application, then brings users to be interested in increasing the frequency of use as a result of user satisfaction to convey their satisfaction to others. (4) Perceived usefulness has a positive and significant effect on Actual usage,more useful an application in accelerating a work process, so it will bring users to be interested in increasing the frequency of use. (5) Attitude toward using has a positive and significant effect on Actual usage, more positive the Attitude toward using an application, the more users are interested in increasing the frequency of use.